Coordination in natural resource management - Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2009)
Because of their spatial scale, most irrigation systems, forests, rangelands, and fisheries cannot be managed at the individual or household level (Knox McCulloch, Meinzen-Dick, and Hazell 1998). They require some form of coordinated regulation to limit overuse and ensure that there is sufficient investment to sustain the resource base. Even the adoption of “lumpy” technologies (such as equipment) that are not cost effective for a single farm requires some form of coordination.